1994
DOI: 10.1089/aid.1994.10.977
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Utility of Cerebral Proton Magnetic Resonance Spectroscopy in Monitoring HIV Infection and Its Associated Neurological Impairment

Abstract: Neurological manifestations of HIV disease occur in most adults and children with AIDS. Many of those affected will inevitably suffer clinical neurological deficits involving mental function, movement, and sensation. Surprisingly, there are not as yet adequate monitoring systems to predict the onset and/or progression of HIV infection of the CNS. Neurological, neuropsychological, CSF, and magnetic resonance imaging (MRI) analyses cannot accurately detect mental deterioration during advancing HIV disease. Repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…We found no significant differences in choline-containing compound (Cho)͞Cr levels between patients and controls, an observation in agreement with a previous report (20). However, other studies have shown increased Cho as a common finding in HIV-1-infected patients (22,24,25,27,36,39).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found no significant differences in choline-containing compound (Cho)͞Cr levels between patients and controls, an observation in agreement with a previous report (20). However, other studies have shown increased Cho as a common finding in HIV-1-infected patients (22,24,25,27,36,39).…”
Section: Discussionsupporting
confidence: 93%
“…MRS studies on patients with HIV carried out with larger voxels in different regions of the brain have shown a correlation between the reduction in NAA and the severity of cognitive impairment (20,22,23,26,27). Our study shows that the decrease of NAA͞Cr in the frontal lobe correlates both with the degree of ADC and with neuropsychological measures of frontal lobe dysfunction, suggesting that ADC may be directly related to the degree of neuronal loss or dysfunction in the frontal cortex.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Magnetic resonance imaging and computed tomography are often used for the patient with AIDS to diagnose Nocardia asteroides infection (11), brain abnormalities (12,13), toxoplasmosis (14), and cytomegalovirus infections in the central nervous system (15). Toxoplasmosis, AIDS-associated myocarditis, abnormal bowel activity, and lymphocyte infiltration of salivary glands have been studied using 67Ga-citrate (16)(17)(18).…”
mentioning
confidence: 99%